2002
DOI: 10.1021/om020651z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the In-Solution Molecular Structure of Reactive Osmium Compounds Involved in the Synthesis of Vicinal Diols

Abstract: Extended X-ray absorption fine structure spectroscopy, EXAFS, has been used to determine the in-solution structure of the two principal reactive components involved in the production of vicinal diols by olefin dihydroxylation using osmium tetroxide. These components are osmium tetroxide (OsO4) and the corresponding diester osmium glycolate complex. The results show that initially the osmium tetroxide molecules are found free and unbound in the investigated solvent (6:1 tertiary butanol in water), with a molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…To image copolymer assemblies by TEM, polymer solutions were stained by OsO 4 vapor, which reacts with double bonds in poly(isoprene) blocks so that the polymer aggregates become more electron-dense and appear as dark regions in TEM images. The staining process might also help stabilize the assemblies by forming cross-links through osmate diesters . The resulting TEM micrographs showed that all nine polymers formed aggregates in aqueous solutions, with greater assembly sizes corresponding with longer isoprene blocks within each polymer series.…”
Section: Resultsmentioning
confidence: 99%
“…To image copolymer assemblies by TEM, polymer solutions were stained by OsO 4 vapor, which reacts with double bonds in poly(isoprene) blocks so that the polymer aggregates become more electron-dense and appear as dark regions in TEM images. The staining process might also help stabilize the assemblies by forming cross-links through osmate diesters . The resulting TEM micrographs showed that all nine polymers formed aggregates in aqueous solutions, with greater assembly sizes corresponding with longer isoprene blocks within each polymer series.…”
Section: Resultsmentioning
confidence: 99%
“…23 This would clearly tell us that any Os(VI) glycolate liganded with an amine spontaneously shifts to complexation with an amine-N-oxide when it is homogeneously conditioned to subsequently furnish Os(VIII) trioxoglycolate 11 [ox] . 24 Reoxidation of Os(VI) dioxoglycolate 11 to give Os(VIII) trioxoglycolate 11 [ox] is comparatively favorable over hydrolysis under neutral conditions, and alkene osmylation by 11 [ox] is highly exergonic and has a modest barrier. 21 Therefore, the second cycle should outpace the hydrolysis of Os(VIII) 11 [ox] or hydrolysis of Os(VI) 11 under typical Upjohn or homogeneous conditions.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…This result increases markedly the precision of the experimental bond-length determination with respect to the results of previous studies by Seip and Stølevik and Dı́az-Moreno and Bowron . As seen in Table , the spread in ab initio predictions is rather large (0.1 Å) compared to the present determination, which can be used as a precise reference point.…”
Section: Resultsmentioning
confidence: 99%
“…15−21 With no permanent dipole moment, no pure rotational spectroscopy has yet been recorded, and the existing structural experimental data have been obtained by X-ray diffraction, 22 electron diffraction, 23 and, more recently, extended X-ray absorption fine structure (EXAFS). 24 X-ray diffraction data have indicated a 1.74(2) Å bond length with a slight (0.03 Å) asymmetry caused by short-range molecular interactions, but electron diffraction and EXAFS data on diluted molecules converged toward a 1.712(3) Å value. These values rely in all cases upon various approximations to account for thermal excitation effects (only about 30% of the molecules are in their ground state at room temperature; see below) and, thus, it seems desirable to obtain more accurate structural data for the ground state, or even better, corrected for zero-point energy effects to enable a rigorous comparison with quantum-chemical calculations.…”
Section: ■ Introductionmentioning
confidence: 96%
See 1 more Smart Citation